2016
DOI: 10.2527/jas.2016-0426
|View full text |Cite
|
Sign up to set email alerts
|

Short-term energy restriction during late gestation of beef cows decreases postweaning calf humoral immune response to vaccination1

Abstract: Our objectives were to evaluate the pre- and postweaning growth and measurements of innate and humoral immune response of beef calves born to cows fed 70 or 100% of NEm requirements during the last 40 d of gestation. On d 0 (approximately 40 d before calving), 30 multiparous Angus cows pregnant to embryo transfer (BW = 631 ± 15 kg; age = 5.2 ± 0.98 yr; BCS = 6.3 ± 0.12) were randomly allocated into 1 of 10 drylot pens (3 cows/pen). Treatments were randomly assigned to pens (5 pens/treatment) and consisted of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…These findings suggest that the CRTL responded better to the immune challenge which may be due to a better development of the immune system during prenatal phase. Also, these data are in agreement with Moriel et al [ 18 ], who using part of the same data used in this study, showed that 70% of energy restriction during the last 40 days of gestation decreased post-weaning vaccination-induced humoral immunity, inflammatory, and physiological stress responses in calves. Our results support the hypothesis that maternal energy restriction during pregnancy can alter gene expression in the offspring associated with immune response which may reflect on the productive performance of the animal.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that the CRTL responded better to the immune challenge which may be due to a better development of the immune system during prenatal phase. Also, these data are in agreement with Moriel et al [ 18 ], who using part of the same data used in this study, showed that 70% of energy restriction during the last 40 days of gestation decreased post-weaning vaccination-induced humoral immunity, inflammatory, and physiological stress responses in calves. Our results support the hypothesis that maternal energy restriction during pregnancy can alter gene expression in the offspring associated with immune response which may reflect on the productive performance of the animal.…”
Section: Resultssupporting
confidence: 93%
“…From weaning (day 0) until 40 days post weaning (dpw), calves were assigned to a preconditioning period. Additional detailed information regarding the nutritional information of the diets, feeding strategies, and the design of the study has been described in Moriel et al [ 18 ] .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, metabolic acidosis in calves born to cows fed low DCAD diets prepartum did not change the efficiency of IgG absorption [8]. Similarly, calves from dams receiving anionic salts before calving −100 mEq/kg DM) had similar serum IgG concentrations (15.1 vs. 14.4 g/L) and apparent efficiency of absorption compared to calves born from control dams [38].…”
Section: Discussionmentioning
confidence: 92%
“…Reduced DMI during the late stage of gestation does not always have negative consequences for the birth weight of calves. For example, restricting beef cows to 70% of their net energy requirements for the last 40 days prior to calving did not affect the weight of their calves [38]. Collazos et al [8] reported that extending the duration of feeding acidogenic diets (−70 and −180 mEq/kg DM) from 21 to 42 d prepartum reduced the average birth weight of calves from 42.9 to 40.0 kg; which is similar to the numerical difference in birth weight between calves from low Ca and low DCAD cows (−2.2 kg) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences noted in plasma cortisol and haptoglobin herein, supplementing AAC or INR to gestating beef cows resulted in similar vaccine efficacy in the offspring. Maternal nutrition has been shown to impact offspring humoral response to vaccination against BRD pathogens ( Moriel et al, 2016 ); however, research is still limited and warranted in this area ( Cooke, 2019 ).…”
Section: Resultsmentioning
confidence: 99%